AgWise Data Sourcing module - Llanos Herrera, Lizeth; Aguilar Ariza, Andres; Bendito, Eduardo; Worku, Wuletawu Abera (2025)
AgWise data sourcing module is toolkit for downloading, processing, and visualizing key satellite imagery, climate and soil properties, digital elevation model, and other spatial layers. All data acquisition is performed using the Google Earth Engine (GEE) platform.